Route Planning Algorithm Based on Irradiation Requirements for Laser-Guided Airborne Ground Weapons - Haoyu, Yuan; Tingting, Li; Chenguang, Wang (2024 International Conference on Communications, Computing, Cybersecurity, and Informatics (CCCI), 2024)
When a UAV (unmanned air vehicle) attacks the ground, after launching a laser-guided weapon, the UAV must continuously irradiate the target to guide the weapon to attack. Numerous restrictions stem from aircraft capabilities, capabilities of airborne equipment, and weapon use needs. We develop a general algorithm for route planning to comply with requirements. It can automatically plan the irradiation section route considering airspace and weapon requirements and adjust the route type (S-type or V-type) before irradiating. It also evaluates if the aircraft's irradiation equipment can continuously target from bomb release to the end of irradiation. In addition, we identify the flight segment position that cannot be irradiated and determine the duration of the aircraft interrupting the irradiation at each position.